An increase in accident and emergency presentations for adverse events following immunisation after introduction of the group B meningococcal vaccine: an observational study. Issue 10 (9th August 2017) - Nainani, Viveka; Galal, Ushma; Buttery, Jim; Snape, Matthew D
Abstract : Objectives: To determine whether the introduction of the capsular group B meningococcal vaccine (4CMenB) in the UK has increased presentations of infants to emergency departments with adverse events following immunisation (AEFI). Participants, design and setting: A retrospective review of hospital records of infants aged 1–6 months presenting to Oxford University Hospitals NHS Trust's emergency departments from September 2013 to August 2016 with discharge diagnoses of vaccine reactions or non-specific conditions. Immunisation history was checked by reference to centralised immunisation records. Main outcome measures: Presentation classifications were 'probable vaccine reaction' (ie, symptoms within 48 hours of immunisation; no alternative cause found), 'possible vaccine reaction' (symptoms within 48 hours of immunisation with a possible alternative cause) or 'not related' (clear alternative diagnosis or not immunised within previous 48 hours). Results: Prior to 4CMenB introduction (2013–15), an annual average of 12 infants presented with probable or possible AEFIs, increasing to 38 infants in the year following 4CMenB introduction (2015/2016). Rates of AEFIs per 1000 immunisation episodes increased post-4CMenB introduction from 1.03 to 3.4 (p<0.001) at 2 months and from 0.14 to 1.13 (p=0.005) at 4 months. At 3 months, when 4CMenB is not given, no increase was seen (p=0.380). 4CMenB introduction was also associated with increased AEFI-related hospital admissions, invasive investigations and intravenous antibiotic use. Conclusions: The increase in emergency department attendances, investigations and antibiotic use for AEFIs following 4CMenB immunisation may influence the cost-effectiveness of the 4CMenB immunisation campaign.